'Sometimes I like to see what I am doing': studying outdoor play pedagogical documentation from children's perspectives. Issue 1 (2nd January 2019) - Kim, Bora
ABSTRACT: This study explores how children respond to and think about their outdoor play pedagogical documentation, and how they engage in outdoor play experiences after they have conversations about their documentation panel. The data source for this study is composed of the author's observations, and individual interviews with six children. A typological analysis model was used to analyse the collected data [Hatch, J. (2002). Doing qualitative research in education settings . Albany, NY: State University of New York Press]. The findings demonstrate that having conversations about documentation allowed the children to articulate their thoughts about previous outdoor play experiences, and provoke and implement further outdoor play ideas. Finally, a critical discussion on the findings of the study is presented in terms of how children's perspectives on outdoor play pedagogical documentation can be utilized to promote the quality of pedagogy in outdoor practice.